Subcutaneous Fat Necrosis of the Newborn: Report of Five Cases - Leire González Lara; Asunción Vicente Villa; María Mercedes Otero Rivas; Mariona Sunol Capella; Fredy Prada; María Antonia González Enseñat (Elsevier, 2017)
Subcutaneous fat necrosis of the newborn (SCFN) is a rare, self-limited disorder of the panniculus which appears in the first few weeks of life. SCFN generally follows an uncomplicated course. However, there are important complications for which the patient must be regularly monitored, including thrombocytopenia, hypoglycemia, hypertriglyceridemia, and most importantly, hypercalcemia. We report five infants with SCFN. All children were born at term. The onset of lesions was between 1 day and 20 days after birth. The back was the most frequent location. Birth hypoxia was the most frequent risk factor. Complications included hypercalcemia, hypoglycemia, and metastatic calcifications (disseminated subcutaneous calcifications, nephrocalcinosis, and myocardial calcifications). This study provides the first case of SCFN in the context of hypoxic encephalopathy and refractory septic shock that required extracorporeal membrane oxygenation (ECMO).